2008
DOI: 10.1111/j.1574-695x.2008.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydiae and polymorphonuclear leukocytes: unlikely allies in the spread of chlamydial infection

Abstract: While much is known about the attachment of the chlamydiae to the host cell and intracellular events during the developmental cycle, little is known about the mechanism(s) by which elementary bodies exit the cell. In this report, we use the guinea pig conjunctival model of Chlamydia caviae infection to present in vivo ultrastructural evidence supporting two mechanisms for release of chlamydiae from the mucosal epithelia. Four days after infection, histopathologic observation shows an intense infiltration of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
(29 reference statements)
0
33
0
Order By: Relevance
“…Thus, increased gonococcal colonization due to chlamydial infection may lead to increased transmission from a coinfected female to a male partner. In addition, the spread of Chlamydia both to the upper reproductive tract of the infected host and to an uninfected partner may be facilitated by the host PMN response, as proposed by Rank et al from studies with C. caviae in a guinea pig genital tract infection model (64). The increased PMN influx observed in coinfected female mice might then be expected to lead to increased transmission from a coinfected female to a male partner.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, increased gonococcal colonization due to chlamydial infection may lead to increased transmission from a coinfected female to a male partner. In addition, the spread of Chlamydia both to the upper reproductive tract of the infected host and to an uninfected partner may be facilitated by the host PMN response, as proposed by Rank et al from studies with C. caviae in a guinea pig genital tract infection model (64). The increased PMN influx observed in coinfected female mice might then be expected to lead to increased transmission from a coinfected female to a male partner.…”
Section: Discussionmentioning
confidence: 81%
“…It was also of interest in our dose-response experiments that at two doses (10 3 and 10 4 IFU), AZ 2 actually reached higher levels than SP 6 . That PMNs are an active participant in the conjunctival C. caviae infection was visualized by us in a recent transmission electron microscopy study (11). We reported that C. caviae was restricted to infection of the superficial epithelial cells and that PMNs were the only inflammatory cell in contact with chlamydia-infected cells.…”
Section: Discussionmentioning
confidence: 84%
“…It is widely accepted that the neutrophil is viewed as a professional phagocyte whose sole function in immunity is to engulf, kill, and clear bacteria in response to infection. However, neutrophils have been implicated in host tissue damage in Chlamydial infections, including guinea pig ocular chlamydial infection models (51). Recent investigations into the role of neutrophil involvement in Chlamydia pathogenesis revealed that neutrophil depletion dramatically decreased ocular pathology both clinically and histologically and that there was an associated alteration in adaptive immunity (26).…”
Section: Discussionmentioning
confidence: 99%